Ghana's landscape approach to REDD+: Is it decentralizing or recentralizing power? - Kumeh, Eric Mensah; Hirons, Mark; McDermott, Constance L.; Ramcilovic-Suominen, Sabaheta (Pergamon Press, 2025)
This paper examines the devolution of powers over land, trees, and carbon through an institutional innovation in Ghana known as the Hotspot Intervention Area (HIA) governance mechanism. HIAs, which form a core part of the Ghana Cocoa Forest REDD+ (Reducing Emissions from Deforestation and Degradation) Programme (GCFRP), employs a “landscape approach” to reduce deforestation, focusing on devolving power and distributing carbon and non-carbon benefits to local communities. We apply decentralization theory and the concept of “bundles of power” to assess which powers have (not) been decentralized through HIAs. Our analysis draws on the pilot case of the Juabeso Bia Landscape, combining 13 focus groups, 21 key informant interviews, and a review of written documents to examine: 1) the internal organization of the JBL HIA itself, and 2) how this interacts with the wider national and international landscapes of governance and climate finance. We found that the HIA governance mechanism has formally established four-tier decision-making structure that grant multiple decision-making roles and assign land and forest resources protection responsibilities to committees within local Community Resource Management Areas (CREMAs) and high-level HIA bodies. However, in practice, the powers devolved to these entities are largely confined to the internal operations and administrative functions of the established committees and landscape management board within the HIA. Meanwhile, Ghana’s broader legal structures and the priorities associated with accessing international carbon finance are reinforcing the authority of external actors, such as multilateral finance institutions, in governing land, trees, and carbon within the study localities. The study highlights that devolving the power to distribute carbon finance locally, without a corresponding devolution of rule-making power over natural resources to community-based institutions, risks reinforcing rather than transforming existing power structures. This imbalance constrains local actors’ ability to determine how their land, tree and carbon are managed to meet their own needs and priorities. Broader, cross-institutional policy reforms are required to enable local communities to renegotiate their rights to access and benefit from land and forest resources.
Keywords: multi-actor governance; environmental justice; forest-farm nexus; landscape approaches; CREMAs; Just Globe